LA EXISTENCIA HUMANA EN PERSPECTIVA. ANÁLISIS DE LA NOVELA “LA CASA” DEL ESCRITOR RICARDO DÍAZ BORREGALES (De la Crítica, 2024)
The article has a series of contributions from the theory of literary analysis and existentialism as a philosophical current that delves into the problems of being as an entity from the individual to the collective. The purpose of the research was to delve into the philosophical cognitive aspects that literature can reach through the construction of fictional narratives using as a basis the work "La casa" by Ricardo Díaz Borregales. The method used was dialectics with which the discourse of the characters of the selected work was analyzed in depth in the search for the elements of existentialism that determine the human being from the philosophical point of view. As conclusions it is obtained that "The house" can be classified as an existentialist novel, where there is a realistic fictional elaboration in which both the effective reality and the philosophical perspective of philosophical existentialism are projected, which is shown by the writer through his literary language